Anti-Inflammatory and Antioxidant Activities of Eugenol: An Update - Renan Oliveira Silva Damasceno; João Lucas Silva Pinheiro; Lucas Henrique Marques Rodrigues; Rebeca Carneiro Gomes; Allana Brunna Sucupira Duarte; Jeremias Justo Emídio; Lúcio Ricardo Leite Diniz; Damião Pergentino de Sousa (MDPI AG, 2024)
Medicinal plants are a rich source of bioactive compounds that possess pharmacological properties for preventing and treating inflammation-related diseases. Essential oils is a chemical class that contains many bioactive compounds, such as eugenol, which is capable of inhibiting or modulating the inflammatory response. This natural product emerges as a compound that promotes various biological activities, including antioxidant activity, which makes it useful in the food industry. Recently, its pharmacological applications have also been highlighted. So, this review aims to update and discuss the most recent findings on the anti-inflammatory and antioxidant activities of eugenol, along with its mechanisms of action and therapeutic potential for treating inflammation and oxidative imbalance conditions.